Conditional process model: Technology readiness, work motivation, subjective well-being, and moderation of work ethic in improving lecturer performance in the digital ERA - Nanda, Giri Dwi; Mubyl, Mutiarini; Hernawan, Hernawan (Edelweiss Applied Science and Technology, 2026)
This study develops and tests a conditional process model examining the effect of Technology Readiness (TR) on lecturer performance, mediated by Work Motivation (MOT) and Subjective Well-Being (SWB), and moderated by Work Ethic (WE). An explanatory sequential mixed-methods design was employed. Quantitative data were collected from 115 lecturers in LLDIKTI Region IX and analyzed using Conditional Process Analysis with SmartPLS 4.0, while qualitative data were obtained through focus group discussions with 12 senior lecturers and analyzed thematically. The findings indicate that TR does not have a significant direct effect on lecturer performance but indirectly influences performance through its positive effects on MOT and SWB. Both MOT and SWB significantly enhance performance and serve as key mediating variables. In addition, WE negatively moderates the relationship between MOT and performance, suggesting that a stronger work ethic may weaken the positive impact of motivation. Qualitative findings highlight generational differences in technology adaptation and the importance of institutional support. Overall, this study demonstrates that psychological factors are more immediate drivers of lecturer performance than technology readiness alone, implying that lecturer development strategies should integrate digital capability enhancement with initiatives that strengthen motivation and psychological well-being in the digital era.